STUDY OF MICROBIOLOGICALLY INDUCED CORROSION OF 5083 ALUMINIUM ALLOY BY SULFATE-REDUCING BACTERIA IN SEAWATER - Putu Riska Agustina, Luh
The main issue often occurs in the ship hull is corrosion. Although the primary material for ship hull has good corrosion resistance (AA5083), but still pitting corrosion inevitably happens. It’s because there are many chloride ions contained in seawater. The corrosion behavior of aluminium alloys in seawater is also influenced by the presence of bacteria that can accelerate or inhibit the corrosion process. This study aims to determine the influence of sulfate-reducing bacteria on the corrosion of AA5083 alloy in seawater. Bacillus aryabhattai use in this experiment as one of sulfate-reducing bacteria group and seawater comes from Santolo Beach, Garut, West Java.